2022
DOI: 10.15835/nbha50112562
|View full text |Cite
|
Sign up to set email alerts
|

Promoter activity analysis and transcriptional profile of Ginkgo biloba 1-Deoxy-D- Xylulose 5-Phosphate reductoisomerase gene (GbDXR) under abiotic stresses

Abstract: Terpene trilactones (TTL) is a pharmacological ingredient in Ginkgo biloba and its content has become one of the key indices for medicinal value evaluation of ginkgo. 1-Deoxy-D-xylulose 5-phosphate reductoisomerase (DXR) catalyzes the first step specific for isopentenyl diphosphate production in methylerythritol phosphate pathway, which provide the basic structure required for TTLs biosynthesis. To understand the mechanism controlling the GbDXR gene expression, the GbDXR promoter sequence was isolated and subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…DXR catalyzes DXP to generate MEP, which is an important rate limiting enzyme in the MEP pathway and an ideal target for regulating the MEP pathway [ 8 ]. In a study focusing on the DXR gene promoter of G. biloba , we found that WRKY, MYB, MYC, and AP2/ERF binding sites exist in its upstream regulatory elements, and AP2/ERF are important TFs regulating the expression of the DXR gene [ 39 ]. WRKYs were found to be involved in the regulation of other terpenoid synthesis structure genes in G. biloba .…”
Section: Discussionmentioning
confidence: 99%
“…DXR catalyzes DXP to generate MEP, which is an important rate limiting enzyme in the MEP pathway and an ideal target for regulating the MEP pathway [ 8 ]. In a study focusing on the DXR gene promoter of G. biloba , we found that WRKY, MYB, MYC, and AP2/ERF binding sites exist in its upstream regulatory elements, and AP2/ERF are important TFs regulating the expression of the DXR gene [ 39 ]. WRKYs were found to be involved in the regulation of other terpenoid synthesis structure genes in G. biloba .…”
Section: Discussionmentioning
confidence: 99%